Goodwill impairment: A comparative study under US GAAP, IFRS, and China GAAP - Shen Huiyue (2020)
According to the current international financial accounting standards (IFRS), goodwill is no longer amortized, but an impairment test should be performed at the end of each year. Once an impairment loss is confirmed, it cannot be reversed. This study aims to compare the causes and impact of the goodwill impairment losses with prior researches. The cases of Kraft Heinz Company, Dalian Zeus Entertainment Co., Ltd, and Bayer Group that disclosed impairment losses in the fiscal year 2018 reporting under US GAAP, China GAAP and IFRS are analyzed and compared. Our findings based on the ROE, ROA, ROS and goodwill-to-assets ratio analysis of these three companies are concluded as (1)goodwill impairment losses harm the overall corporate performance and show lagging information, and (2) goodwill impairment losses are relative with big bath, and (3) irrational mergers and acquisitions and large-scale write-offs prompt opportunistic management.